Photophysical, Photochemical, and Fluorescence Quenching Studies of New Halogenated Phthalocyanine Metal Complexes (Indian Journal of Chemistry (IJC), 2024)
This study provides an accurate description of the preparation of some new quad-compensatory phthalocyanine complexes of Zn(II) and Cu(II) substituted by 4-(4-Bromo-2-formylphenoxy). Several spectroscopic techniques were employed to characterize phthalocyanine metal complexes including FT-IR, NMR, mass spectrometry, and UV-Visible spectrophotometry. Aggregation studies were investigated in various DMSO concentrations ranging from 2×10-6 M to 10×10-6 M. In this research, the bathochromic shift of the Q band of [Zn(Pc)] depended on the solvent type in the following ascending order:  (THF< DMF< CHCl3< DMSO and H2SO4), and for [Cu(Pc)] was (THF< DMSO< DMF< CHCl3 and H2SO4) respectively. Photophysical properties of the resulting complexes were evaluated by measuring factors such as absorption and emission. Spectral results showed that both complexes 2 and 3 have the potential to be used as sensitizers in photodynamic therapy (PDT) based on their singlet oxygen efficiencies (UD = 0.41, 0.39).